Firebrand Waves of Digital Activism 1994-2014 - Karatzogianni, Athina. author. aut Link
VII, 172 p.
Keywords: This book introduces four waves of upsurge in digital activism and cyberconflict. The rise of digital activism started in 1994, was transformed by the events of 9/11, culminated in 2011 with the Arab Spring uprisings, and entered a transformative phase of control and mainstreaming since 2013 with the Snowden affair.